Perubahan Parliamentary Threshold ditinjau dari Asas Kepastian Hukum: Studi Analisis Putusan Mahkamah Konstitusi No.166/PUU-XXI/2023 - Muttaqin, Didik Zainul; Huda, Miftakhul (JOM, 2025)
This research aims to analyze changes to the parliamentary threshold within Indonesia's electoral system and review its compatibility with the principle of legal certainty, particularly following the Constitutional Court Decision No. 166/PUU-XXI/2023. The parliamentary threshold is a technical electoral instrument that determines whether a political party is entitled to obtain seats in the House of Representatives (DPR) based on the national valid vote acquisition. In practice, this threshold has undergone significant changes from 2.5% (2009) to 4% (2019–2024), which has resulted in the elimination of votes for small parties and potentially reduces the constitutional rights of voters. This study utilizes a normative juridical approach with descriptive-qualitative analysis techniques to examine the relevant laws and regulations and Constitutional Court decisions. The findings indicate that the determination of the threshold figure has not been based on transparent, proportional, and fair academic arguments. Constitutional Court Decision No. 166/PUU-XXI/2023 reinforces the importance of the principle of legal certainty in formulating threshold policies so as not to undermine citizens' political participation and not contradict the principle of popular sovereignty. This research recommends that the parliamentary threshold be re-evaluated through a comprehensive and inclusive academic study, in order to realize an electoral system that is fairer, more proportional, and aligned with the principles of constitutional democracy.